IMPLEMENTASI MODEL PEMBERDAYAAN MASYARAKAT DALAM EDUKASI KEUANGAN SYARIAH BAGI GURU DAN MAHASISWA DI PEKANBARU - Muhammad Ali Aqsa; Herman Herman; Dinda Genta Wicara; Teguh Hendra; Nurhayana Nurhayana; J Ardan Mardan; Khonelis Dehotman; Ul-fa Niah (Jurnal Pengabdian Kompetitif, 2026)
This study implemented the modified Indonesian Community Empowerment Model (MPMI-S) to enhance Sharia financial literacy among teachers and students in Pekanbaru. The collaborative program between STIE Riau and Pegadaian Syariah Cabang Sudirman involved 30 teachers and 150 students, using the Participatory Action Research (PAR) method. Conducted in three learning cycles, it focused on three pillars: local capacity strengthening, collaborative mentoring, and community-driven sustainability. Results show effective synergy, with the partnership evolving from formal cooperation into an organic collaboration, supported by intensive communication and complementary roles. Integrating Sharia values into educational materials increased program relevance, which significantly improved participants' understanding and led to the formation of the independent Pekanbaru Sharia Investment Community. Thus, the MPMI-S model serves as an effective and contextual framework for sustainable Sharia financial education.